Implementation Of Multicultural Education Values In Islamic Boarding School - Aris Wahyudi; Yusqi Mahfuds; Wanda Saputri Machmud (LP2M UIN KH.Achmad Siddiq Jember, 2023)
Indonesia has a motto known as 'Bhineka Tunggal Ika'. This motto means although they are different but still one, this is because Indonesia has a diversity of tribes, cultures, races, and languages. The inability of some individuals in Indonesia to accept these differences leads to negative multiculturalism. In pesantren, this will be more sensitive because the students have a diversity of backgrounds both in terms of culture, ethnicity, ethnicity, language, and regions which are then united in the same place. Multicultural education is defined as education that teaches differences and the vitality of cultural diversity and ethnicity related to equality, justice, openness, and recognition of differences. This study aims to determine the inculcation of the value of multicultural education, especially at the Al-Fatah Islamic Boarding School, Temboro. This research is a descriptive qualitative using a phenomenological approach, which is a study that aims to objectively reveal facts, symptoms, and events related to the phenomenon of planting and values ​​of multicultural education at the Al-Fataah Islamic Boarding School, Temboro. This research is also included in the field research category. The results of the study found the inculcation of multicultural educational values ​​that emphasize the importance of legitimacy, and the vitality of ethnic and cultural diversity in shaping the order of life, groups, and nations by inculcating democratic values ​​to using strategies that involve approaches to parents.